LOS VIEJOS PANTEONES, MAUSOLEOS Y CENOTAFIOS DEL CEMENTERIO Y CAMPO DE HELLÍN (ALBACETE). SUS PROGRAMAS ICONOGRÁFICOS Y ARTÍSTICOS - Jordan Montes, J.F (Imafronte, 1997)
Analysis of the iconographical programmes that appear in the pantheons and mausoleums of the cementary in the city of Hellin. The modernist pantheon of the Navarro family and thegothic one of the Izquierdo family are amongst the mosf notable examples. In the,former there are allusions to classical mythology and in the latter the figures of the Virtudes. In the paper there is un analysis of two cenofaphs Ni the country side around Hellin, the one in Navas de Leza is interesting for its architecture as well as, for its inscriptions.